Desafios e possibilidades da regularização fundiária no processo de herança intergeracional da agricultura familiar no município de Silvânia-GO - Ximenes, Sara de Lima Saeghe Alcanfor (2022)
In order to access some public policies, the family farmer needs to have his rural property in good standing, and its non-compliance may lead to competitive limitations, as an example, the promotion of policies such as the National Program for the Strengthening of Family Farming (PRONAF) and the National Program for Land Credit (PNCF). To address the problem, the study aims to investigate the challenges, causes, consequences and possibilities of addressing the lack of legal equity regularity in the process of intergenerational inheritance in family farming in the municipality of Silvânia-GO, delimiting two local communities as objects of study and the obligations related to the processes of patrimonial succession, considering the legal framework, the entry into force of the Civil Code/2002. This exploratory and documental research describes the scenario, including the period of SarsCov-2, the COVID-19 pandemic, the laws in force that are applied to family farmers, as benefits and main legal confrontations. The research analyzed the reasons for not regularizing, and, if this has already been done, the farmers' access or not to public policies. As a result, it was observed that the heirs who regularized their lands did so by means of judicial inventory and usucaption, an unusual institute for generational inheritance issues. The heirs who remain on the land are mostly middle-aged and elderly, and do not know about the public policies described above or, if they do, they have not accessed them.